Assessing environments of commercialization of innovation for SMEs in the global wine industry: A market dynamics approach - Agostino Menna; Philip R. Walsh (Wine Economics and Policy, 2019)
Small and medium enterprises (SMEs) can play an important role in the diffusion of wine innovation. Employing a market dynamics approach where the interaction of producers (supply) and buyers (demand) are seen to influence innovation creation, a conceptual framework is applied to the global wine industry to identify commercialization strategies for SMEs. The framework identifies four commercialization environments or clusters; Innovation Nirvana, Innovation Push, Innovation Pull and Innovation Wasteland as determined by the principle market dimensions of wine supply (innovation-push) and wine demand (market-pull). A k-means cluster analysis is undertaken on twenty-two wine-producing member countries of the OECD to determine which jurisdictions occupy each of the four clusters. The study results is a diverse distribution of old world and new world wine producing countries across all of the identified commercialization environments. Conclusions about national commercialization environments and related strategies for wine industry entrepreneurs are presented. These findings have implications for wine industry SMEs, investors and agri-policy makers.
Keywords: 330; Innovation; Global wine industry; OECD